2015
DOI: 10.1037/bne0000050
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of nucleus accumbens dopamine D1-family receptors in renewal of alcohol seeking after punishment-imposed abstinence.

Abstract: In humans, places or contexts previously associated with alcohol use often provoke relapse during abstinence. This phenomenon is modeled in laboratory animals using the ABA renewal procedure, where alcohol seeking that is suppressed with extinction training in a context (B) renews when the animal returns to the original training context (A). However, extinction training does not adequately capture the motivation for abstinence in human alcoholics who typically self-initiate abstinence due to the negative conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Finally, NAc dopamine is known to play a role in food reward (Wise, 2004), and from this perspective the observation that hM4Di inhibition of local Drd1-or Drd2-expressing neurons has no effect on food self-administration and seeking is unexpected. However, in our study we trained our mice under low effort (FR1) reinforcement schedule and under these training conditions, we and others found that NAc injections of SCH23390 have no effect on food selfadministration in rats (Bossert et al, 2007;Marchant and Kaganovsky, 2015). Our negative food data using a chemogenetic approach in mice and the previous negative data mentioned above using intracranial drug injections agree with Salamone's (2016) notion of the selective role of NAc dopamine in controlling high-effort but not low-effort food-reinforced responding.…”
Section: Methodological and Experimental Considerationssupporting
confidence: 83%
“…Finally, NAc dopamine is known to play a role in food reward (Wise, 2004), and from this perspective the observation that hM4Di inhibition of local Drd1-or Drd2-expressing neurons has no effect on food self-administration and seeking is unexpected. However, in our study we trained our mice under low effort (FR1) reinforcement schedule and under these training conditions, we and others found that NAc injections of SCH23390 have no effect on food selfadministration in rats (Bossert et al, 2007;Marchant and Kaganovsky, 2015). Our negative food data using a chemogenetic approach in mice and the previous negative data mentioned above using intracranial drug injections agree with Salamone's (2016) notion of the selective role of NAc dopamine in controlling high-effort but not low-effort food-reinforced responding.…”
Section: Methodological and Experimental Considerationssupporting
confidence: 83%
“…It is also unlikely that motor deficits or other non-specific behavioral effects of the drugs decreased context-induced reinstatement, because we previously found that bilateral injections of M+B into vSub or SCH 23390 into NAc shell have no effect on high rate food-reinforced responding (Bossert et al 2007; Bossert and Stern 2014; Marchant and Kaganovsky 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Results from several studies indicate a critical role of nucleus accumbens (NAc) core in context-induced relapse to alcohol seeking after either extinction or punishment. NAc core injections of muscimol+baclofen or the dopamine D1-family receptor antagonist SCH23390 decrease context-induced relapse to alcohol seeking after extinction, and NAc core SCH23390 injections decrease context-induced relapse after punishment (Chaudhri et al 2008 , 2010 ; Marchant and Kaganovsky 2015 ). It is currently unknown whether NAc core plays a similar role in context-induced relapse to cocaine seeking after punishment or extinction.…”
Section: Brain Mechanisms Of Context-induced Relapse After Extinctionmentioning
confidence: 99%
“…This model is a modified ABA renewal procedure in which abstinence is achieved in context B, despite alcohol availability, by punishment with response-contingent electric footshock. Using this model, we have demonstrated context-induced relapse to both alcohol and cocaine seeking when rats were tested in context A after punishment-imposed abstinence in context B (Marchant et al 2014 , 2016 ; Marchant and Kaganovsky 2015 ; Pelloux et al 2018a , b ). Our model and findings extend previous research in the addiction field on the use of punishment procedures to model the negative consequences of drug seeking and drug use (Deroche-Gamonet et al 2004 ; Marchant et al 2013b ; Panlilio et al 2003 ; Pelloux et al 2007 ; Vanderschuren et al 2017 ; Vanderschuren and Everitt 2004 ; Wolffgramm and Heyne 1995 ).…”
Section: Introductionmentioning
confidence: 99%